2020
DOI: 10.5815/ijwmt.2020.01.04
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Mechanism of MANET Network Layer Based Security Attack Prevention

Abstract: The infrastructure benefits, which are achieved from the MANET architecture is the prime reason for the increase in usage for various purposes. The MANET architecture is made truly seamless with the capabilities of working without the central base stations or without the intervention of the central administration. The architecture for a MANET network is highly diversified and completely depends on the formation as the nodes in the MANET network can roam freely with a subsequent connection to any external devic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Mahaboob et al, [14] suggested the attacks types for each network layer are identified and addressed to be prevented. The measures listed in this work are convertible as a modular component of any automated framework to make the complete attack prevention mechanism automated.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mahaboob et al, [14] suggested the attacks types for each network layer are identified and addressed to be prevented. The measures listed in this work are convertible as a modular component of any automated framework to make the complete attack prevention mechanism automated.…”
Section: Literature Reviewmentioning
confidence: 99%